A Series of Yeast Shuttle Vectors for Expression of cDNAs and Other DNA Sequences - Brunelli, J.P.; Pall, M.L.
Expressionlshuttle vectors for the yeast Saccharomyces cerevisiae have usually been large plasmids with only one or a small number of sites that are suitable for cloning and expression. We report here the construction and properties of a series of 12 expression vectors with multiple (four to eight)unique sites in their polylinkers which allow directional cloning and expression of DNA sequences under four different promoters. Eleven of these plasmids replicate at high copy number in Escherichia coli, and all have the yeast TRPl gene, and the 2 pm origin including REP3 sequence, allowing selection and high copy number replication in yeast. Six of the plasmids are designed for the construction and selection of cDNA libraries from various eukaryotic organisms, allowing directional cloning and expression of cDNAs. All of these six have similar polylinkers containing a unique promoter proximal EcoRI site and a unique promoter distal XhoI site, allowing for directional cloning and expression of ZAP'-type cDNAs. cDNAs that complement a wide variety of yeast mutants can be selected from libraries constructed in this way. The four alternative promoters, ADH2, PGK, GAL10 and SV40 were compared for their relative activity, both in E. coli and in yeast. All yeast promoters showed substantial activity in E. coli with ADH2 showing the highest activity. ADH2 also was well-regulated in yeast, showing very high relative activity under derepressing conditions. cDNAs selected by genetic complementation from libraries constructed in these vectors should be easily subclonable into other vectors, allowing expression in different eukaryotic organisms, DNA sequencing or site-directed utagenesis.
Keywords: 2 PM ORI PLASMID; DIRECTIONAL CDNA CLONING; GENETIC COMPLEMENTATION; POLYLINKERS; SHUTTLE VECTORS; CDNA LIBRARIES; COLEL REPLICATION CONTROL